The Effect of Transformational Leadership Style and Interpersonal Competence on Work Motivation of Health Workers - Harefa, Karnirius (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: Community Health Centers (Puskesmas) play a crucial role in providing basic health services. However, the work motivation of health workers is often affected by high workloads, limited infrastructure, and the complexity of cases handled. Objective: This study aimed to analyze the influence of transformational leadership style and interpersonal competence on the work motivation of health workers at Bandar Khalifah Health Center, Percut Sei Tuan District. Research Methods: A quantitative approach with a correlational design was used. A total of 40 health workers were selected using a total sampling technique. Data were collected through a Likert-scale questionnaire and analyzed using Pearson correlation and multiple linear regression with SPSS software. Results:The results showed a significant positive influence between transformational leadership style and work motivation (r = 0.650; p < 0.05) as well as between interpersonal competence and work motivation (r = 0.680; p < 0.05). Regression analysis indicated that transformational leadership (? = 0.480; p = 0.000) and interpersonal competence (? = 0.420; p = 0.004) significantly contributed to improving health workers' work motivation.Conclusion:Transformational leadership style and interpersonal competence significantly influence the improvement of health workers' work motivation. Strengthening these factors is recommended to enhance performance and the quality of health services.